The Effects of Endophytic Beauveria bassiana Inoculation on Infestation Level of Planococcus ficus, Growth and Volatile Constituents of Potted Greenhouse Grapevine (Vitis vinifera L.) - Siphokazi Moloinyane; Felix Nchu (Toxins, 2019)
Endophytic entomopathogenic fungi are being explored for the management of phytophagous insect pests. The effects of Beauveria bassiana (Hypocreales) inoculation of grape plants on the infestation level of P. ficus, tissue nutrient contents, and growth and volatile constituents of potted grape plants were assessed. Grapevine plants were individually inoculated with a suspension of 1 × 108 conidia mL−1 of B. bassiana by drenching before experimentally infesting each of them with thirty adult females of P. ficus. At four weeks post-treatment, the fungus was re-isolated from leaves of 50% of the fungus-exposed plants. However, no significant difference (p > 0.05) was observed in all the plant growth parameters measured in the fungus-treated and control plants. Plant tissue analysis revealed markedly higher contents of calcium (Ca) and magnesium (Mg) in the leaf tissue of plants exposed to the B. bassiana relative to the control. Gas chromatography mass spectrometry (GC-MS) analyses showed that a significantly (X2 = 5.1; p < 0.02) higher number of known anti-insect volatile compounds (nine) were present among fungus treated plants compared to the control plants (five). Naphthalene, which is toxic to insects and humans, was detected only in the volatiles of the fungus-exposed plants. B. bassiana did not have any significant effect on total polyphenol, alkaloid, and flavonoids. Overall, treatment with fungus did not inhibit the infestation by P. ficus. In conclusion, these findings shed light on some of the mechanisms involved in endophytic fungus-plant-insect interactions.